Challenges and perceptions of implementing mass testing, treatment and tracking in malaria control: a qualitative study in Pakro sub-district of Ghana - Ignatius Cheng Ndong; Daniel Okyere; Juliana Yartey Enos; Alfred Amambua-Ngwa; Corinne Simone C. Merle; Alexander Nyarko; Kwadwo Ansah Koram; Collins Stephan Ahorlu (BMC, 2019)
Abstract Background Malaria remains endemic in Ghana despite several interventions. Studies have demonstrated very high levels of asymptomatic malaria parasitaemia in both under-five and school-age children. Mass testing, treatment and tracking (MTTT) of malaria in communities is being proposed for implementation with the argument that it can reduce parasite load, amplify gains from the other control interventions and consequently lead to elimination. However, challenges associated with implementing MTTT such as feasibility, levels of coverage to be achieved for effectiveness, community perceptions and cost implications need to be clearly understood. This qualitative study was therefore conducted in an area with on-going MTTT to assess community and health workers' perceptions about feasibility of scale-up and effectiveness to guide scale-up decisions. Methods This qualitative study employed purposive sampling to select the study participants. Ten focus group discussions (FGDs) were conducted in seven communities; eight with community members (n = 80) and two with health workers (n = 14). In addition, two in-depth interviews (IDI) were conducted, one with a Physician Assistant and another with a Laboratory Technician at the health facility. All interviews were recorded, transcribed, translated and analyzed using QSR NVivo 12. Results Both health workers and community members expressed positive perceptions about the feasibility of implementation and effectiveness of MTTT as an intervention that could reduce the burden of malaria in the community. MTTT implementation was perceived to have increased sensitisation about malaria, reduced the incidence of malaria, reduced household expenditure on malaria and alleviated the need to travel long distances for healthcare. Key challenges to implementation were doubts about the expertise of trained Community-Based Health Volunteers (CBHVs) to diagnose and treat malaria appropriately, side effects of Artemisinin-based Combination Therapies (ACTs) and misconceptions that CBHVs could infect children with epilepsy. Conclusion The study demonstrated that MTTT was perceived to be effective in reducing malaria incidence and related hospital visits in participating communities. MTTT was deemed useful in breaking financial and geographical barriers to accessing healthcare. The interventions were feasible and acceptable to community members, despite observed challenges to implementation such as concerns about CBHVs' knowledge and skills and reduced revenue from internally generated funds (IGF) of the health facility.